1979
DOI: 10.1111/j.1476-5381.1979.tb17337.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ADENOSINE 5′‐TRIPHOSPHATE (ATP) AND Β‐γ‐METHYLENE ATP ON THE RAT URINARY BLADDER

Abstract: High concentrations of adenosine 5′‐triphosphate (ATP, 100 to 1000 μm) were required to cause contraction of the rat urinary bladder, while adenosine and adenosine 5′‐monophosphate (AMP, 1 to 50/im) produced relaxation. One hundred fold lower concentrations of β‐γ‐methylene ATP, which is resistant to degradation to AMP and adenosine, caused dose‐dependent, phasic contractions which mimicked atropine‐resistant responses to nerve stimulation. Adenosine and AMP caused dose‐dependent inhibition of carbachol‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 25 publications
1
47
1
Order By: Relevance
“…These ideas are summarized in the scheme shown in Figure 7. Support for this model is found in the studies by Brown et al (1979) who demonstrated that ADO reduces the carbachol-induced rat bladder contractions. However, Brown et al.…”
Section: Discussionmentioning
confidence: 81%
“…These ideas are summarized in the scheme shown in Figure 7. Support for this model is found in the studies by Brown et al (1979) who demonstrated that ADO reduces the carbachol-induced rat bladder contractions. However, Brown et al.…”
Section: Discussionmentioning
confidence: 81%
“…Similar studies of purine nucleotide potencies have been carried out in a number of other tissues and a comparative agonist potency order has been demonstrated (see . In the guinea-pig vas deferens (Fedan et al, 1982;Burnstock et al, 1983;, the rat and guinea-pig urinary bladder (Brown et al, 1979;Burnstock et al, 1983), the perfused pancreas vascular bed (Chapal & Loubatieres-Mariani, 1983), the rat aorta and femoral artery White et al, 1985) and the rabbit ear artery (Kennedy & Burnstock, 1985a), P2-purinoceptors mediate contraction. A rank potency order of a,fi-methylene, 0,ymethylene ATP > ATP = 2-methylthio ATP is indicated in these tissues.…”
Section: Pharmacologymentioning
confidence: 99%
“…ATP produces a rapidly developing phasic bladder contraction and is considered a likely noncholinergic excitatory transmitter at this level (Brown et al, 1979;Bo & Burnstock, 1990;Brading & Williams, 1990;Luheshi & Zar, 1990). After the early suggestion of Holton & Holton (1954) and Holton (1959), a role for ATP as a sensory transmitter has been recently reconsidered (Jahr & Jessell, 1983;Fyffe & Perl, 1984).…”
Section: Introductionmentioning
confidence: 99%